Guar gum oleate-graft-poly(methacrylic acid) hydrogel as a colon-specific controlled drug delivery carrier. (20th February 2017) - Seeli, D. Sathya; Prabaharan, M.
Highlights: Guar gum based pH-responsive hydrogel was synthesized as a colon drug carrier. The prepared hydrogel was characterized with FT-IR, 1 H NMR and XRD analysis. This hydrogel showed a pH dependent swelling and drug release profile, which would be suitable for colon-targeted drug delivery. This hydrogel showed no cytotoxicity against the MSC stem cells and therefore it would be safe material for colon-drug delivery. Abstract: A novel type of ethylene glycol dimethacrylate (EGDMA) cross-linked guar gum oleate- graft- poly(methacrylic acid) (GGO- g -PMAc) hydrogel was prepared as a pH-responsive controlled release carrier for colon-specific drug delivery. The structure of GGO- g -PMAc hydrogel was characterized by FT-IR, 1 H NMR and X-ray diffraction (XRD) analysis. The swelling degree of the GGO- g -PMAc hydrogel at pH 7.4 was found to be higher than that at pH 1.2. The drug release studies performed in pH 7.4 and 1.2 buffer solutions at 37 °C revealed that the rate and amount of drug released from the GGO- g -PMAc hydrogel at pH 7.4 were higher than that at pH 1.2. The MTT assay revealed that there is no noticeable cytotoxicity of GGO- g -PMAc hydrogel at the concentration range of 0–100 μg/ml against the mouse mesenchymal stem cell line (C3H10T1/2). These results suggested that GGO- g -PMAc hydrogel can be a prospective pH-sensitive carrier for colon-targeted drug delivery.